Preparation and characterization of NaI-Na3PO4 sodium ion conducting solid electrolyte with PLLTMEDA as an additive for sodium batteries / Noorazmi Hassan - Hassan, Noorazmi (Institute of Graduate Studies, UiTM, 2017)
New binary inorganic salt sodium iodide (NaI)–sodium phosphate (Na3PO4) prepared by mechanical milling for 3 hours and low sintering temperature method at 50 ºC exhibits maximum ionic conductivity of (1.02±0.19) × 10−4 S cm−1 at room temperature for the composition 0.50 NaI : 0.50 Na3PO4. The increase in conductivity is due to the increase in number of mobile Na+ charge carriers through the conducting pathway provided by tetrahedral structures of Na3PO4. The presence of P–O at wavenumber 580 cm−1 and PO4 3− bands at wavenumber 1012 cm−1 respectively were detected by the infrared technique. Fourier transform infrared spectroscopy had been shifted indicating changes in polyhedral structure which in turn led to the formation of conducting channel by corner sharing or through edges. The spectra also implies that chelation of iodide anion gave rise to high mobility and elevations of the charge carriers to traverse along the conducting pathway created from tetrahedral phosphate thus giving rise to the conductivity of the sample. However the ionic conductivity value is still not high enough for application in electrochemical devices. Improve conductivity can be achieved by incorporation of an additive to the binary system. Poly(L-Leucine)1,3-diamino propane (PLLTMEDA) has been chosen as an additive due to its unique properties that able to further increase the ionic conductivity. The electrical conductivity of NaI–Na3PO4 and NaI– Na3PO4–PLLTMEDA were obtained by employing impedance spectroscopy (IS) technique…